Effect of modified boron nitride nanosheets on mechanical properties and thermal conductivity of carboxylated nitrile rubber - Song Wan-cheng1, Li Xue-yu1, Lu Shao-jie1, Amel Mohamed1, Zhu Yu-hong2, Wen Yan-rong1,2, Jia Hong-bing1 (Hecheng xiangjiao gongye, 2021)
In order to improve the physical and mechanical properties and thermal conductivity of carboxyl nitrile rubber (XNBR), boron nitride was stripped by chemical stripping method, and modified boron nitride nano sheets (PBNNS) were prepared by modifying boron nitride nano sheets with polyvinylpyrrolidone. The effects of the amount of PBNNS on the mechanical and thermal conductivity of XNBR were investigated. The results showed that when the dosage of PBNNS was 3 phr, the comprehensive properties of PBNNS / XNBR vulcanizate were better. The tensile strength, elongation at break, 100% constant tensile stress and 300% constant tensile stress were increased by 52.4%, 5.0%, 27.4% and 38.0% respectively, and the thermal conductivity was increased by 41.9%.